MENERAPKAN KEDISIPLINAN MASYARAKAT TERHADAP KEBERSIHAN LINGKUNGAN - Anis Khoiriyah; Fatinatus Selvia (Kalam Nusantara Institute, 2023)
Creating community discipline towards environmental cleanliness is a shared responsibility, especially the community around the environment. They have an important role in protecting the environment and creating a clean and healthy environmental culture. One interesting phenomenon is that the level of discipline and public awareness of environmental cleanliness is still lacking. It can be seen that there is still a lot of garbage scattered and piled up in the neighborhood around them, places such as the village office that are rarely cleaned and also the ditches that are deliberately dammed by one of the residents so that this can cause health problems and environmental hygiene. The problems in this research are (1) how is the perception of the people of Kalidandan Village on environmental cleanliness, (2) what efforts are made by the people of Kalidandan Village to maintain the cleanliness of their environment, (3) how the people of Kalidandan Village apply discipline in maintaining cleanliness in their environment. This study aims to describe the level of discipline of the Kalidandan Village community in maintaining the cleanliness of their environment which focuses on the views, attitudes and behavior of the community related to community discipline towards environmental cleanliness, while the indicators in this study to determine the level of community discipline towards their environment are: a) public perception of the cleanliness of their environment b) community attitudes in realizing discipline in maintaining a clean environment c) behavior, namely the community's efforts to maintain a clean living culture. The results of the study show that in general the people of Kalidandan Village know the importance of maintaining environmental cleanliness and health for their survival, but in fact the awareness and behavior of the community in maintaining cleanliness in their environment is not in accordance with this understanding, so that most of the people of Kalidandan Village do not have a disciplined attitude. in maintaining the cleanliness of the environment, this is caused by the lack of public awareness of the condition of the cleanliness of the environment around them, the influence of the existing environment in the community where some people lack awareness and understanding of the community about environmental hygiene.